Klima-Jobs erfordern zusätzliche Kompetenzen : nachgefragte Kompetenzen in der Wind- und Solarbranche. Eine Analyse von Online-Stellenanzeigen - Engler, Jan Felix [Verfasser]; Mertens, Armin [Verfasser]; Neligan, Adriana [Verfasser] (Bertelsmann Stiftung, 2024)
„Um die Wirtschaft mithilfe von Solarenergie und Windkraft klimaneutral gestalten zu können, werden Menschen mit unterschiedlichen Berufen, Fachkenntnissen und Fähigkeiten benötigt. Diese Studie untersucht die Kompetenzbedarfe für 13 ausgewählte Berufe. Basis dafür ist eine umfassende computerlinguistische Analyse von Online-Stellenanzeigen. Darin betrachten wir die nach gefragten Kompetenzen für die Bereiche Wind- und Solarenergie und vergleichen sie mit der branchenübergreifenden Nachfrage.“ (Hrsg.; BIBB-Doku)

„Renewable energies are the core of the energy transition and the basis for achieving climate neutrality. Their expansion requires 300,000 additional skilled workers in solar and wind energy in Germany. However, these skilled workers must be appropriately qualified, as the solar and wind industry requires special skills compared to other sectors. This is the key finding of a Jobmonitor analysis of almost 2.7 million online job advertisements. In the solar industry, special skills are expected above all from specialists in roofing and plumbing, heating and air conditioning technology, and in the wind industry particularly from professions in the fields of electronics and mechatronics. In order to close the skills and specialist skills gap in the renewable energies sector, further training is needed for people with a vocational qualification (or professional experience) and partial qualifications for unskilled workers. The combination of different professions to become a renewable energy specialist could also attract workers to one of the most important industries of the future and should be examined.“ (editor; BIBB-Doku)
Keywords: G 1.2.4.1.5 Energie- und Wasserversorgung; G 1.2.3.1 Potenziale; 370; 330; Windindustrie; Solarenergie; Erneuerbare Energie; Energiewirtschaft; Kompetenzprofil; Qualifikationsbedarf; Stellenanzeige; Analyse